(untitled) (Research, Society and Development, 2022)
Introduction: Diabetes is a metabolic decompensation of various origins. There are 3 types of Diabetes Mellitus: type 1 or insulin dependent; type 2 or non-insulin dependent and gestational diabetes. A pregnancy that develops with Gestational Diabetes Mellitus (GDM) is classified as high risk. The treatment of Diabetes Mellitus in general is multifactorial, evidenced by changing the patient’s habits. Objective: The aim of this study is to describe the pathophysiological aspects of GDM and its consequences for the pregnant woman and the fetus, in addition to identifying its possible causes, risks and treatment. Methodology: The study was developed in the face of a systematic review. Results: 10 articles that met the criteria previously determined by the study were selected, where the main results highlighted dietary, behavioral, age and overweight factors as risk factors for GDM. Result and discussions: In addition to emphasizing the importance of early diagnosis in prenatal care, where all professionals have their importance during treatment. Conclusion: With this research it can be concluded that gestational diabetes mellitus needs more attention from the public and private network. It is necessary to create strategies in education and health regarding knowledge about diabetes mellitus and how it can be avoided.